Climate and human stressors on global penguin hotspots: Current assessments for future conservation - Míriam Gimeno; Joan Giménez; Andre Chiaradia; Lloyd S. Davis; Philip J. Seddon; Yan Ropert‐Coudert; Ryan R. Reisinger; Marta Coll; Francisco Ramírez (Global Change Biology, 2024)
As charismatic and iconic species, penguins can act as “ambassadors” or flagship species to promote the conservation of marine habitats in the Southern Hemisphere. Unfortunately, there is a lack of reliable, comprehensive, and systematic analysis aimed at compiling spatially explicit assessments of the multiple impacts that the world's 18 species of penguin are facing. We provide such an assessment by combining the available penguin occurrence information from Global Biodiversity Information Facility (>800,000 occurrences) with three main stressors: climate‐driven environmental changes at sea, industrial fisheries, and human disturbances on land. Our analyses provide a quantitative assessment of how these impacts are unevenly distributed spatially within species' distribution ranges. Consequently, contrasting pressures are expected among species, and populations within species. The areas coinciding with the greatest impacts for penguins are the coast of Perú, the Patagonian Shelf, the Benguela upwelling region, and the Australian and New Zealand coasts. When weighting these potential stressors with species‐specific vulnerabilities, Humboldt ( Spheniscus humboldti ), African ( Spheniscus demersus ), and Chinstrap penguin ( Pygoscelis antarcticus ) emerge as the species under the most pressure. Our approach explicitly differentiates between climate and human stressors, since the more achievable management of local anthropogenic stressors (e.g., fisheries and land‐based threats) may provide a suitable means for facilitating cumulative impacts on penguins, especially where they may remain resilient to global processes such as climate change. Moreover, our study highlights some poorly represented species such as the Northern Rockhopper ( Eudyptes moseleyi ), Snares ( Eudyptes robustus ), and Erect‐crested penguin ( Eudyptes sclateri ) that need internationally coordinated efforts for data acquisition and data sharing to understand their spatial distribution properly.

Contrasting patterns of tree species mixture effects on wood δ13C along an environmental gradient - G. de Streel; C. Collet; I. Barbeito; K. Bielak; A. Bravo-Oviedo; G. Brazaitis; L. Coll; L. Drössler; D. Forrester; M. Heym; M. Löf; M. Pach; et al. (European Journal of Forest Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Brassinosteroids promote growth, fruit quality and protection against Botrytis on Fragaria x ananassa - R. N. Furio; S. M. Salazar; G. M. Martínez-Zamora; Y. Coll; V. Hael-Conrad; J. C. Díaz-Ricci (European Journal of Plant Pathology, 2019)

Effect of natural and synthetic Brassinosteroids on strawberry immune response against Colletotrichum acutatum - R. N. Furio; P. L. Albornoz; Y. Coll; G. M. Martínez Zamora; S. M. Salazar; G. G. Martos; J. C. Díaz Ricci (European Journal of Plant Pathology, 2019)

Homogenization and analysis of an expanded long‐term monthly rainfall network for the Island of Ireland (1850–2010) - S. Noone; C. Murphy; J. Coll; T. Matthews; D. Mullan; R. L. Wilby; S. Walsh (International Journal of Climatology, 2016)
Long‐term precipitation series are critical for understanding emerging changes to the hydrological cycle. To this end we construct a homogenized Island of Ireland Precipitation ( IIP ) network comprising 25 stations and a composite series covering the period 1850–2010, providing the second‐longest regional precipitation archive in the British‐Irish Isles. We expand the existing catalogue of long‐term precipitation records for the island by recovering archived data for an additional eight stations. Following bridging and updating of stations HOMogenisation softwarE in R ( HOMER ) homogenization software is used to detect breaks using pairwise and joint detection. A total of 25 breakpoints are detected across 14 stations, and the majority (20) are corroborated by metadata. Assessment of variability and change in homogenized and extended precipitation records reveal positive (winter) and negative (summer) trends. Trends in records covering the typical period of digitization (1941 onwards) are not always representative of longer records. Furthermore, trends in post‐homogenization series change magnitude and even direction at some stations. While cautionary flags are raised for some series, confidence in the derived network is high given attention paid to metadata, coherence of behaviour across the network and consistency of findings with other long‐term climatic series such as England and Wales precipitation. As far as we are aware, this work represents the first application of HOMER to a long‐term precipitation network and bodes well for use in other regions. It is expected that the homogenized IIP network will find wider utility in benchmarking and supporting climate services across the Island of Ireland, a sentinel location in the North Atlantic.

Growth and yield of mixed versus pure stands of Scots pine (Pinus sylvestris L.) and European beech (Fagus sylvatica L.) analysed along a productivity gradient through Europe - H. Pretzsch; M. del Río; Ch. Ammer; A. Avdagic; I. Barbeito; K. Bielak; G. Brazaitis; L. Coll; G. Dirnberger; L. Drössler; M. Fabrika; D. I. Forrester; et al. (European Journal of Forest Research, 2015)

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Valuing acorn dispersal and resprouting capacity ecological functions to ensure Mediterranean forest resilience after fire - C. Puerta-Piñero; L. Brotons; L. Coll; J. R. González-Olabarría (European Journal of Forest Research, 2012)

A simple equation for determining sea surface emissivity in the 3–15 µ m region - R. Niclòs; V. Caselles; E. Valor; C. Coll; J. M. Sánchez (International Journal of Remote Sensing, 2009)

Evaluation of the B ‐method for determining actual evapotranspiration in a boreal forest from MODIS data - J. M. Sánchez; V. Caselles; R. Niclós; E. Valor; C. Coll; T. Laurila (International Journal of Remote Sensing, 2007)

Geographic variations in seed dispersal by ants: are plant and seed traits decisive? - R. Boulay; J. Coll-Toledano; A. J. Manzaneda; X. Cerdá (The Science of Nature, 2007)

Medical speciality and pattern of medicines prescription - A. Vallano; E. Montan; J. M. Arnau; X. Vidal; C. Pallars; M. Coll; J. R. Laporte (European Journal of Clinical Pharmacology, 2004)

Abstracts of Presentations at the 18th Conference of the Entomological Society of Israel - M. P. Pener; L. Anshelevich; E. Dunkelblum; M. Hard; A. Harari; D. Gordon; M. Kehat; H. Reuveny; O. Akunis; D. Oppenheim; E. Dunkelblum; Acta Rafaeli; et al. (Phytoparasitica, 2001)

Abstracts of papers presented at the 16th conference of the Entomological Society of Israel Research on thrips in Israel Dedicated to the Memory of Prof. E. Rivnay on the 100th Anniversary of his Birth - M. Wysoki; M. Wysoki; M. Klein; M. Davidovich; R. Shaked; K. Rosenfeld; E. Pressman; Phyllis G. Weintraub; A. R. Horowitz; Sophia Kleitman; R. Azari; Leah Tsror; et al. (Phytoparasitica, 1999)

In situ measurements of skeletal muscle power output using new capacitive strain gauge - P. G. Cooper; G. J. Wilson; D. T. A. Hardman; O. Kawaguchi; Y. -F. Huang; A. Martinez-Coll; R. Carrington; E. Puchert; R. Crameri; C. Horam; S. N. Hunyor (Medical & Biological Engineering & Computing, 1999)

A model to study fish DNA immersion vaccination by using the green fluorescent protein - M. Fernandez‐Alonso; F. Alvarez; A. Estepa; R. Blasco; J. M. Coll (Journal of Fish Diseases, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Effects of elevated CO 2 and O 3 on the rate and duration of grain growth and harvest index in spring wheat (Triticum aestivum L.) - B. J. MULHOLLAND; J. CRAIGON; C. R. BLACK; J. J. COLLS; J. ATHERTON; G. LANDON (Global Change Biology, 1998)
Wheat ( Triticum aestivum L.) cv. Minaret was grown in open‐top chambers (OTCs) in 1995 and 1996 under three carbon dioxide (CO 2 ) and two ozone (O 3 ) levels. Plants were harvested regularly between anthesis and maturity to examine the rate of grain growth (dG/dt; mg d –1 ) and the rate of increase in harvest index (dHI/dt;% d –1 ). The duration of grain filling was not affected by elevated CO 2 or O 3 , but was 12 days shorter in 1995, when the daily mean temperature was over 3 °C higher than in 1996. Season‐long exposure to elevated CO 2 (680 μmol mol –1 ) significantly increased the rate of grain growth in both years and mean grain weight at maturity (MGW) was up to 11% higher than in the chambered ambient air control (chAA; 383 μmol mol –1 ). However, the increase in final yield obtained under elevated CO 2 relative to the chAA control in 1996 resulted primarily from a 27% increase in grain number per unit ground area. dG/dt was significantly reduced by elevated O 3 under ambient CO 2 conditions in 1995, but final grain yield was not affected because of a concurrent increase in grain number. Neither dG/dt nor dHI/dt were affected by the higher mean O 3 concentrations applied in 1996 (77 vs. 66 nmol mol –1 ); the differing effects of O 3 on grain growth in 1995 and 1996 observed in both the ambient and elevated CO 2 treatments may reflect the contrasting temperature environments experienced. Grain yield was nevetheless reduced under elevated O 3 in 1996, primarily because of a substantial decrease in grain number. The data obtained show that, although exposure to elevated CO 2 and O 3 individually or in combination may affect both dG/dt and dHI/dt, the presence of elevated CO 2 does not protect against substantial O 3 ‐induced yield losses resulting from its direct deleterious impact on reproductive processes. The implications of these results for food production under future climatic conditions are considered.

Growth, light interception and yield responses of spring wheat ( Triticum aestivum L.) grown under elevated CO 2 and O 3 in open‐top chambers - B. J. Mulholland; J. Craigon; C. R. Black; J. J. Colls; J. Atherton; G. Landon (Global Change Biology, 1998)
Spring wheat cv. Minaret was grown to maturity under three carbon dioxide (CO 2 ) and two ozone (O 3 ) concentrations in open‐top chambers (OTC). Green leaf area index (LAI) was increased by elevated CO 2 under ambient O 3 conditions as a direct result of increases in tillering, rather than individual leaf areas. Yellow LAI was also greater in the 550 and 680 μmol mol –1 CO 2 treatments than in the chambered ambient control; individual leaves on the main shoot senesced more rapidly under 550 μmol mol –1 CO 2 , but senescence was delayed at 680 μmol mol –1 CO 2 . Fractional light interception ( f ) during the vegetative period was up to 26% greater under 680 μmol mol –1 CO 2 than in the control treatment, but seasonal accumulated intercepted radiation was only increased by 8%. As a result of greater carbon assimilation during canopy development, plants grown under elevated CO 2 were taller at anthesis and stem and ear biomass were 27 and 16% greater than in control plants. At maturity, yield was 30% greater in the 680 μmol mol –1 CO 2 treatment, due to a combination of increases in the number of ears per m –2 , grain number per ear and individual grain weight (IGW). Exposure to a seasonal mean (7 h d –1 ) of 84 nmol mol –1 O 3 under ambient CO 2 decreased green LAI and increased yellow LAI, thereby reducing both f and accumulated intercepted radiation by ≈ 16%. Individual leaves senesced completely 7–28 days earlier than in control plants. At anthesis, the plants were shorter than controls and exhibited reductions in stem and ear biomass of 15 and 23%. Grain yield at maturity was decreased by 30% due to a combination of reductions in ear number m –2 , the numbers of grains per spikelet and per ear and IGW. The presence of elevated CO 2 reduced the rate of O 3 ‐induced leaf senescence and resulted in the maintenance of a higher green LAI during vegetative growth under ambient CO 2 conditions. Grain yields at maturity were nevertheless lower than those obtained in the corresponding elevated CO 2 treatments in the absence of elevated O 3 . Thus, although the presence of elevated CO 2 reduced the damaging impact of ozone on radiation interception and vegetative growth, substantial yield losses were nevertheless induced. These data suggest that spring wheat may be susceptible to O 3 ‐induced injury during anthesis irrespective of the atmospheric CO 2 concentration. Possible deleterious mechanisms operating through effects on pollen viability, seed set and the duration of grain filling are discussed.

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)